2013
DOI: 10.1051/0004-6361/201220025
|View full text |Cite
|
Sign up to set email alerts
|

Clouds in the atmospheres of extrasolar planets

Abstract: Context. Owing to their wavelength-dependent absorption and scattering properties, clouds have a strong impact on the climate of planetary atmospheres. The potential greenhouse effect of CO 2 ice clouds in the atmospheres of terrestrial extrasolar planets is of particular interest because it might influence the position and thus the extension of the outer boundary of the classic habitable zone around main sequence stars. Such a greenhouse effect, however, is a complicated function of the CO 2 ice particles' op… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
36
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 37 publications
(55 reference statements)
5
36
0
Order By: Relevance
“…It would be useful in future to compare them with more sophisticated schemes such as are currently used for Earth climate studies [e.g., Khairoutdinov and Randall, 2001]. In addition, it has been suggested recently that the two-stream approach to radiative transfer calculations (which we use) may be inaccurate for CO 2 cloud scattering [Kitzmann et al, 2013]. If this is the case, it would mean that our peak temperatures in Figure 11 are slightly overestimated.…”
Section: 1002/2015je004787mentioning
confidence: 99%
“…It would be useful in future to compare them with more sophisticated schemes such as are currently used for Earth climate studies [e.g., Khairoutdinov and Randall, 2001]. In addition, it has been suggested recently that the two-stream approach to radiative transfer calculations (which we use) may be inaccurate for CO 2 cloud scattering [Kitzmann et al, 2013]. If this is the case, it would mean that our peak temperatures in Figure 11 are slightly overestimated.…”
Section: 1002/2015je004787mentioning
confidence: 99%
“…On the other hand, the optical properties of particles with sizes larger than a few micrometers are essentially flat in the visible and near IR (e.g., Kitzmann et al, 2010). Compared to the cloud-free cases, this would lead to a constant offset in the planetary albedo, which is almost independent from the incident stellar radiation (see, e.g., Kitzmann et al, 2011 for H 2 O clouds andKitzmann et al, 2013 for CO 2 clouds).…”
Section: Ice-albedo Feedback and Atmospherementioning
confidence: 99%
“…(7.67) and (7.71) in Petty (2006)]. Among the cases we examined, only the case with S cr 5 1 and N * 5 5 3 10 24 kg 21 provides a combination of particle radius (35 mm) and cloud optical thickness (t ; 5), which is within the range favorable for scattering greenhouse effect (Mischna et al 2000;Forget et al 2013;Kitzmann et al 2013). In other cases, the cloud development seems to be too infrequent, or the cloud layer is optically too thick.…”
mentioning
confidence: 94%
“…Investigation of possible structures of circulation fields and properties of clouds in such an atmosphere, especially a dense CO 2 atmosphere, is not only interesting as a problem of fluid mechanics, but also as an important target of research on the early Mars, where the scattering greenhouse effect of CO 2 ice cloud could have played an indispensable role in maintaining possible warm climate (Forget and Pierrehumbert 1997;Mischna et al 2000;Colaprete and Toon 2003;Mitsuda 2007;Forget et al 2013). Previous studies have shown that the intensity of scattering greenhouse effect depends on a number of cloud properties, such as the size distribution of cloud particles, optical depth, cloud cover, and cloud height (Forget and Pierrehumbert 1997;Mischna et al 2000;Kitzmann et al 2013). For the advancement of our understanding on the early Martian climate, it is, therefore, valuable to investigate possible properties of CO 2 clouds consistent with circulation fields of convection associated with condensation of the major atmospheric constituent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation